Child mental health and educational attainment: Multiple observers and the measurement error problem - David W. Johnston; Carol Propper; Stephen Pudney; Michael A. Shields (Institute for the Study of Labor (IZA), 2011)
We examine the effect of survey measurement error on the empirical relationship between child mental health and personal and family characteristics, and between child mental health and educational progress. Our contribution is to use unique UK survey data that contains (potentially biased) assessments of each child's mental state from three observers (parent, teacher and child), together with expert (quasi-)diagnoses, using an assumption of optimal diagnostic behaviour to adjust for reporting bias. We use three alternative restrictions to identify the effect of mental disorders on educational progress. Maternal education and mental health, family income, and major adverse life events, are all significant in explaining child mental health, and child mental health is found to have a large influence on educational progress. Our preferred estimate is that a 1-standard deviation reduction in 'true' latent child mental health leads to a 2-5 months loss in educational progress. We also find a strong tendency for observers to understate the problems of older children and adolescents compared to expert diagnosis.
urn:nbn:de:101:1-201108093010
Keywords: C30; I10; I21; J24; 330; child mental health; education; Strengths and Difficulties Questionnaire; measurement error